2021
DOI: 10.1038/s41380-021-01298-5
|View full text |Cite
|
Sign up to set email alerts
|

A triple-network organization for the mouse brain

Abstract: The triple-network model of psychopathology is a framework to explain the functional and structural neuroimaging phenotypes of psychiatric and neurological disorders. It describes the interactions within and between three distributed networks: the salience, default-mode, and central executive networks. These have been associated with brain disorder traits in patients. Homologous networks have been proposed in animal models, but their integration into a triple-network organization has not yet been determined. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 53 publications
(84 reference statements)
9
83
0
Order By: Relevance
“…S8, A and B). Given the putative causal control of the anterior insular cortex (AI) on the Frontal module of the DMN (26,53), we also examined the effects of LC-NE activation on their FC changes and found that CNO-evoked activation significantly enhanced anticorrelation between AI and DMN frontal module (fig. S8, C and D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S8, A and B). Given the putative causal control of the anterior insular cortex (AI) on the Frontal module of the DMN (26,53), we also examined the effects of LC-NE activation on their FC changes and found that CNO-evoked activation significantly enhanced anticorrelation between AI and DMN frontal module (fig. S8, C and D).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, systemic administration of these agents indiscriminately targets all NE-producing neurons in the brain and sympathetic nervous system, making it difficult determine the role of the LC-NE in modulating the DMN. Though selective manipulation of LC-NE while imaging DMN is currently impossible in humans due to technical and ethical constraints (7,19), such studies are feasible in rodent models since structural and functional homologs of the human DMN have been identified in mice (20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the rat salience network converged by functional and structural connectivity as is reported in Tsai et al (2020) is also included. For mice RSNs, brain regions that are commonly found in Sforazzini et al (2014) and Mandino et al (2021) for DMN and for salience network are included in the table. For other areas, the homologous networks defined in Zerbi et al (2015) are used.…”
Section: Time-averaged Features Of Resting-state Functional Magnetic ...mentioning
confidence: 99%
“…For other areas, the homologous networks defined in Zerbi et al (2015) are used. Finally, the lateral cortical network (LCN), which is postulated to perform the central executive function in rodents, is also included for rats ( Schwarz et al, 2013 ) and for mice ( Mandino et al, 2021 ). Note that the LCN is essentially the same as the somatosensory/motor areas for rodents ( Grandjean et al, 2020 ).…”
Section: Time-averaged Features Of Resting-state Functional Magnetic ...mentioning
confidence: 99%
“…These regions are part of the so-called Salience Network (SN) and are highly responsive to arousing situations in humans (Hermans et al, 2014b) and in mice (Mandino et al, 2021;Zerbi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%